1987
DOI: 10.1042/bj2460519
|View full text |Cite
|
Sign up to set email alerts
|

Clones of human ribosomal DNA containing the complete 18 S-rRNA and 28 S-rRNA genes. Characterization, a detailed map of the human ribosomal transcription unit and diversity among clones

Abstract: We have isolated several new clones of human ribosomal DNA. Each clone contains part of the external transcribed spacer, a complete 18 S-rRNA gene, the internal transcribed spacers, a complete 28 S-rRNA gene and a short downstream flanking region. We present a detailed map of the human ribosomal transcription unit with the locations of numerous useful restriction sites. In particular, a unique NheI site in the 5.8 S-rRNA gene enabled this gene to be mapped with respect to the 18 S-rRNA and 28 S-rRNA genes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 30 publications
4
47
0
2
Order By: Relevance
“…The plasmid pHrB was a gift from J. Sylvester (Wilson, 1982;Maden et al, 1987). The plasmid pHr-BES was a gift from L. Rothblum (Grummt et al, 1982;Miesfeld and Arnheim, 1982).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid pHrB was a gift from J. Sylvester (Wilson, 1982;Maden et al, 1987). The plasmid pHr-BES was a gift from L. Rothblum (Grummt et al, 1982;Miesfeld and Arnheim, 1982).…”
Section: Plasmidsmentioning
confidence: 99%
“…To test the possibility that longer pre-rRNA could recruit more pre-rRNA processing factors, we injected HeLa nuclei with plasmid pHrB that contains the same Pol I promoter, but also has an rDNA sequence that extends through the entire 3700-base pair 5Ј ETS and 1639 base pairs of the 18S rRNA (Wilson, 1982;Maden et al, 1987). As a result, pHrB includes the A 0 and A 1 processing sites ( Figures 4A and 7A).…”
Section: Recruitment Of Some Pre-rrna Processing Factors To Active Simentioning
confidence: 99%
“…rRNAs are transcribed from multigene families and heterogeneity arises from nucleotide substitutions and deletions among the individual rRNA genes. An analysis of human 28S rRNA genes revealed that 28S rRNA comprises a heterogeneous group of RNAs (7,69). These rRNAs were shown to be transcribed and to be present both in monosomes and in polysomes (70).…”
Section: Potential Effects Of Ribosome Heterogeneity On the Filtermentioning
confidence: 99%
“…In addition to the sequence variation that occurs in expansion segments, heterogeneity in the 28S rRNA genes has also been noted in regions that are conserved between species (70). Although 18S rRNA appears to be much less variable than 28S rRNA, some heterogeneity in 18S rRNA genes has also been described (69,74).…”
Section: Potential Effects Of Ribosome Heterogeneity On the Filtermentioning
confidence: 99%
“…The more prominent ones have been identified as expansion segments (7,46), divergent domains (27), or variable regions (17). The variability of some regions is such that closely related organisms such as mice and rats show many sequence differences (26), and sequence differences are even detected in different copies of the rRNA genes (rDNAs) from a single organism (25). These regions are absent in most eubacteria and archaebacteria and present in most eukaryotes (19,46), although exceptions to this rule have recently been found (4,10,43).…”
mentioning
confidence: 99%